Battery swapping station for electric vehicles: opportunities and challenges. Issue 3 (19th May 2020) - Ahmad, Furkan; Saad Alam, Mohammad; Saad Alsaidan, Ibrahim; Shariff, Samir M.
Abstract : In contemporary days, the research and development enterprises have been focusing to design intelligently the battery swap station (BSS) architecture having the prospects of providing a consistent platform for the successful installation of the large‐scale fleet of hybrid and electric vehicles (i.e. xEVs). The BSS may calibrate its subsystem for the electric vehicle (EV) deployment by accomplishing similar idea as in existing gasoline refuelling stations, in which the discharged batteries are being replaced or swapped by partially or fully charged ones by spending a few minutes. The BSS approach has arisen as a promising technology to the traditional EV recharging station approach as it provides a broader experience of business prospects for the specific stakeholders. This work deals with the introduction to BSS including infrastructure, techniques, benefits over charging station and key challenges associated with BSS. Furthermore, an S34X‐smart swapping station for xEVs is proposed and finally, the key thrust is research for BSS is discussed. To the authors' knowledge, this is the first kind of review work on BSS.